Doing Business in Russia and the Other Former Soviet Republics: Accounting and Joint Venture Issues. - Doupnik, Timothy S. (The Accounting Review, 1993)
Abstract Reviews the book "Doing Business in Russia and the Other Former Soviet Republics: Accounting and Joint Venture Issues," by Adolf J.H. Enthoven, Jaroslav V. Sokolov and Alexander M. Petrachkov.